In-silico design, synthesis and biological evaluation of 4-aryl-4H-chromene derivatives as CDK-2 inhibitors: A molecular approach to finding a lead for breast cancer - Sk Md Sohail Amin, Prajakta Harish Patil, Mrunal Desai, Jagadish Puralae Channabasavaiah (Journal of Applied Pharmaceutical Science, 2024)
Breast cancer is a major health concern, with a mortality rate worldwide. Targeted therapy has emerged as a promising option for cancer treatment, particularly through the inhibition of cyclin-dependent kinase-2 (CDK-2), holding a promise for combating this disease. The potential of 4-aryl-4H-chromene derivatives as inhibitors of CDK- 2 was evaluated in this study using the in silico method. Amongst the 38 designed compounds, 13 compounds were identified as potential CDK-2 inhibitors based on their superiority within in silico studies with docking scores ranging from −9.180 to −8.006 Kcal/mol and with favourable absorption, distribution, metabolism, excretion, and toxicity properties. These 13 compounds were later synthesized and characterized using spectral methods. Furthermore, these compounds were assessed for their antioxidant and anticancer properties by in vitro assays. Compounds 2M and 2C displayed notable antioxidant potential with IC50 values of 24.44 and 39.03 μM, respectively, in 2,2-Diphenyl- 1-picrylhydrazyl and 2,2′-casino-bis (3-ethylbenzothiazoline-6-sulfonic acid) assays. The sulforhodamine B assay on Michigan Cancer Foundation-7 (MCF-7) cells indicated that compound 1L demonstrated the strongest growth inhibition activity with an IC50 of 0.2 μM. Five other compounds (2O, 2K, 1C, 2M, and 2J) also exhibited promising activity with IC50 values ranging from 11.74 to 27.2 μM. In conclusion, 4-aryl-4H-chromene derivatives can be considered potential lead candidates for breast cancer treatment.
Keywords: Breast cancer, targeted therapy, 4-aryl-4H-chromene, in-silico, ADMET, one-pot synthesis, antioxidant